2022
DOI: 10.21203/rs.3.rs-2313802/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiome Dynamics Associated with Rifamycin Therapy for Latent Tuberculosis Infection: Findings from a Prospective Cohort Study

Abstract: Background: Latent tuberculosis infection (LTBI) treatment is an effective strategy to eliminate TB in low-incidence settings. Shorter LTBI regimens incorporating the antimicrobial class of rifamycins are designed to improve treatment completion rates. Recent evidence suggests that the rifamycins could induce irreversible gut microbiota changes that impact future anti-TB immunity. Methods: To document the immediate effect of the rifamycins on the gut microbiota, we followed six patients with LTBI initiating fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…INH prophylaxis itself was associated with Blautia enrichment and Moraxella, Megamonas, and Actinobacillus depletion. Other studies have shown Clostridiales-, Coprococcus-, Lachnospiraceae-, and Ruminococcaceae-enriched and Clostrid-ium_XIVa-, Romboutsia-, and Roseburia-depleted stool to occur during rifamycin-based tuberculosis preventive therapy [25]. To our knowledge, our study is the first to show Blautia-enriched and Moraxella-, Megamonas-, and Actinobacillus-depleted stool in humans on isoniazid TB preventive therapy.…”
Section: Discussionsupporting
confidence: 56%
“…INH prophylaxis itself was associated with Blautia enrichment and Moraxella, Megamonas, and Actinobacillus depletion. Other studies have shown Clostridiales-, Coprococcus-, Lachnospiraceae-, and Ruminococcaceae-enriched and Clostrid-ium_XIVa-, Romboutsia-, and Roseburia-depleted stool to occur during rifamycin-based tuberculosis preventive therapy [25]. To our knowledge, our study is the first to show Blautia-enriched and Moraxella-, Megamonas-, and Actinobacillus-depleted stool in humans on isoniazid TB preventive therapy.…”
Section: Discussionsupporting
confidence: 56%